Analytical performance of a high-repetition rate laser head (500 Hz) for HR LA-ICP-QMS imaging. Issue 9 (16th January 2020) - Šala, Martin; Šelih, Vid Simon; Stremtan, Ciprian Cosmin; Teun van Elteren, Johannes
Abstract : Fast aerosol transport technologies used in LA-ICP-MS increased the need for high-repetition rate lasers. We thoroughly investigated the performance of a 500 Hz laser and no damaging effect on the image quality was observed. Abstract : With the advent of low dispersion, fast aerosol transport technologies used in laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), the need for high-repetition rate lasers has become crucial. This work reports on the analytical performance of a LA unit with an experimental 500 Hz laser head, interfaced with a quadrupole ICP-MS instrument, and comprising a commercial two-volume ablation chamber (HelEx II) and low-dispersion aerosol transport device (ARIS). The system was tested for potential problems related to particle saturation, elemental fractionation, ionisation efficiency, etc., prior to validation as a high-resolution LA-ICP-QMS imaging tool with a high mapping rate.